2008
DOI: 10.1021/mp800047v
|View full text |Cite
|
Sign up to set email alerts
|

3-D Tumor Model forIn VitroEvaluation of Anticancer Drugs

Abstract: The efficacy of potential anticancer drugs during preclinical development is generally tested in vitro using cancer cells grown in monolayer; however, a significant discrepancy in their efficacy is observed when these drugs are evaluated in vivo. This discrepancy, in part, could be due to the three-dimensional (3-D) nature of tumors as compared to the two-dimensional (2-D) nature of monolayer cultures. Therefore, there is a need for an in vitro model that would mimic the 3-D nature of tumors. With this objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
277
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(295 citation statements)
references
References 46 publications
17
277
0
1
Order By: Relevance
“…Prior research has suggested that the efficacy of potential anticancer drugs in vivo differs when compared with in vitro studies using cancer cells grown in monolayer (31,44). Because three-dimensional culture of cancer cell lines has long been advocated as a better model of the malignant phenotype in vivo (31, 45), we evaluated the effect of SD-1029 on chordoma cell lines in three-dimensional culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has suggested that the efficacy of potential anticancer drugs in vivo differs when compared with in vitro studies using cancer cells grown in monolayer (31,44). Because three-dimensional culture of cancer cell lines has long been advocated as a better model of the malignant phenotype in vivo (31, 45), we evaluated the effect of SD-1029 on chordoma cell lines in three-dimensional culture.…”
Section: Discussionmentioning
confidence: 99%
“…As cellular architecture may have a significant effect on drug uptake, distribution, and efficacy, drug efficacy may be significantly lower in three-dimensional models in cancer cell lines than in two-dimensional monolayer (31). To evaluate if the growth of chordoma cells could be inhibited by SD-1029 in three-dimensional culture, we measured the effect of SD-1029 on chordoma cell lines.…”
Section: Sd-1029 Blocks Stat3 Pathway and Inhibits Growth Of Chordomamentioning
confidence: 99%
“…In an environment which better mimics the extracellular conditions encountered by cells in vivo, it has been possible to access more accurate information about cell homeostasis, differentiation and migration 1,2 . It is increasingly apparent that the basic 2D cell culture models commonly used fail to provide the cell a microenvironment for adequate adhesion and proliferation resulting in discrepancies between observations made in vitro and in vivo, especially for the testing of potential anticancer drugs 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Findings from such studies have highlighted the importance of cellular architecture, phenotypic variations, and extracellular matrix barrier to drug transport in cellular response to selected compounds. Combination of all these parameters contributes to the overall drug efficacy for that particular cancer or tumor [43]. These studies are aimed at the discovery of multigenic biomarkers with higher probability to better describe complex biology systems.…”
Section: Anti-cancer Therapiesmentioning
confidence: 99%